2016
DOI: 10.1017/cem.2016.119
|View full text |Cite
|
Sign up to set email alerts
|

LO082: EMS response to police use of force events: periods of personal and professional risk in prehospital care

Abstract: Introduction: This study provides an estimate of the number of EMS calls related to police use of force events that involve struggling, intoxicated and/or emotionally distressed patients. We hypothesized there would be under-reporting of EMS risk by paramedic agencies due to lack of standardized reporting of police events by EMS services and lack of a common linked case number between prehospital agencies in Canada. Methods: Data were collected during a multi-site, prospective, consecutive cohort study of poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Consistent with previous findings (e.g., Hall & Votova, 2013), we found that the rate of police UoF incidents, as defined in the "Method" section, in the participating agency is very low (0.07%). with respect to UoF rates, two key findings emerged.…”
Section: Uof Ratessupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous findings (e.g., Hall & Votova, 2013), we found that the rate of police UoF incidents, as defined in the "Method" section, in the participating agency is very low (0.07%). with respect to UoF rates, two key findings emerged.…”
Section: Uof Ratessupporting
confidence: 92%
“…In Canada, it has been estimated that UoF is even more rare. Several reports have suggested that UoF occurs in about 0.10% of all police-public encounters in Canada (e.g., Baldwin et al, 2022;Hall & Votova, 2013), with lethal force occurring in about 0.001% of encounters (RCMP, 2022).…”
Section: Police Uofmentioning
confidence: 99%
“…The results of studies like ours can help inform the development and delivery of realistic and effective operational skills training that approximates real-world stress exposure. This evidence-based training approach is likely to be particularly important for improving performance in UoF encounters, which while low frequency (Hall and Votova, 2013; Baldwin et al, 2018), can result in tragic consequences and present substantial liability for officers and agencies (Braidwood, 2010; MacNeil, 2015; Dubé, 2016). It is also important to point out that studies like ours can also inform the development of SBT content, by informing agencies as to what sort of CFS and incident factors are occurring within their jurisdiction (e.g., if weapons are often accessible in CFS, that should be an element that is built into SBT scenarios).…”
Section: Discussionmentioning
confidence: 99%
“…Armstrong et al (2014) note that scenario-based training will be particularly important for use-of-force encounters, given the relatively low rate at which these encounters occur in real-life settings. Officers are unlikely to gain sufficient experience responding to use-of-force events from their day-to-day calls for service (Baldwin et al , 2018; Hall and Votova, 2013). Nonetheless, they must always be prepared to respond appropriately in case they do find themselves in a situation requiring the use of force, just as they must be prepared to effectively employ de-escalation tactics.…”
Section: Development Of Trainingmentioning
confidence: 99%